Offshoring and the migration of jobs - Gianmarco Ottaviano (IZA World of Labor, 2015)
The impact of offshoring on domestic jobs is more complicated than it first appears. In the standard narrative, offshoring production is thought to harm domestic workers by providing cheap alternative sources of labor. However, while offshoring may directly displace domestic workers, the resulting foreign market access and lower production costs allow domestic firms to increase efficiency, expand production, and thus create new jobs for domestic workers. These new jobs often involve more complex tasks, as revealed by the positive relation between the share of offshored jobs and the average cognitive and interactive task content of domestic jobs.
Keywords: J24; M5; M51; 330; offshoring; employment; tasks; skills